Diversity and ecology of phytophagous weevils in the deciduous fruit industry, South Africa - Magagula, Mxolisi Meshack (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.